The architecture at three Saqqaq sites in the Nuuk Fjord, Greenland - Berglund, Maria (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2003)
AbstractThis article presents the architecture at three Saqqaq sites in the Nuuk Fjord on the West Coast of Greenland. The focus is on the architecture: box hearths, an axial feature and a boulder hearth will be described and accounted for by figures and measurements. Attention will also be paid to the distribution of artifacts, since these configurations might complement the evidence from stone structures when estimating the limits of a specific dwelling. By positioning the structures in the landscape, it will be underlined that architecture is a part of the natural surroundings and vice versa.